Pesticide use in vegetable crops in Pakistan: Insights through an ordered probit model. (September 2017) - Damalas, Christos A.; Khan, Muhammad
Abstract: Pesticide application issues are a major concern in farmers' production practices, but little is known about the knowledge levels and the behaviour of farmers when handling pesticides. Farmers' knowledge of pesticide use practices and factors affecting application of the current practices were explored in the Lodhran and Vehari districts of Pakistan. The ordered probit model was used to analyze data from selected small-scale farmers dealing with vegetable production. All farmers were using chemical pesticides for pest control, but more than one-third of the pesticides belonged to the category highly hazardous (34.2%) or moderately hazardous (35%) pesticides. Moreover, the majority of the farmers were using mixtures for better control of different pests or diseases. Most farmers (58.1%) showed moderate levels of knowledge of common application issues. In addition, only 16.1% of the farmers had received basic training on pesticide use and only 12.9% had access to information. The ordered probit model showed that basic training on pesticide use, access to advice, education, reading pesticide labels, and years of applying pesticides contributed positively to farmers' knowledge of pesticide handling. By contrast, applying pesticide mixtures had a negative impact on farmers' knowledge. Overall, the data shed light on patterns of pesticide handling practices by small-scale farmers in vegetable crops in the Lodhran and Vehari districts of Pakistan, for which research data are lacking from the literature. Over-reliance of farmers on pesticides, poor access to training on pesticides, and poor knowledge of proper handling practices imply high risk of pesticide exposure and pesticide residues on crops. Effective extension programs and smooth access to advice are necessary for improving farmers' knowledge on proper use of pesticides and thus reducing the adverse effects on their health and the environment. Highlights: Farmers' knowledge of pesticide use practices were explored in Pakistan. The majority of the farmers were using mixtures for better control of different pests. Most farmers (58.1%) showed moderate knowledge levels of pesticide application. Only 16.1% of the vegetable farmers had received some basic training on pesticide use. Extension programs are necessary for improving farmers' knowledge on pesticide use.